A metal-responsive interdigitated bilayer for selective quantification of mercury(ii) traces by surface plasmon resonance. Issue 6 (18th February 2016) - Ermakova, Elizaveta; Raitman, Oleg; Shokurov, Alexander; Kalinina, Maria; Selector, Sofiya; Tsivadze, Aslan; Arslanov, Vladimir; Meyer, Michel; Bessmertnykh-Lemeune, Alla; Guilard, Roger
Abstract : An innovative design of reusable SPR chips allowing the quantitative and selective determination of mercury(ii ) at the ppt level is reported. Abstract : Reusable surface plasmon resonance chips allowing the quantitative and selective detection of mercury(ii ) ions in water at the 0.01 nM level are reported. The surface-modified gold sensor consists of a rarefied self-assembled monolayer of octanethiol topped with a Langmuir–Blodgett monolayer of an amphiphilic and highly-specific chelator. The interdigitated architecture confers to the bilayer a high packing density, surface coverage, and binding-group accessibility.